2005
DOI: 10.1097/00006231-200505000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of disease activity in Gravesʼ orbitopathy with different methods: comparison of 99mTc-DTPA and 99mTc-depreotide single photon emission tomography, magnetic resonance imaging and clinical activity scores

Abstract: (99m)Tc-DTPA eye SPET is a potentially useful method, allowing rapid imaging at an acceptable cost. It provides essential supplementary information to traditional CAS in assessing disease activity in Graves' orbitopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 11 publications
0
9
0
3
Order By: Relevance
“…In this respect, the correlation between CAS and orbital MR imaging parameters is vital, but reports about the correlation between CAS and MR imaging parameters are limited [12,14,16]. The edematous change of the orbital tissue increases CAS, and prolongs T2RT of EOMs [2,6,15,17].…”
Section: The Comparison Of Cas 0 Group and Cas 1or2 Group In Maxt2rt mentioning
confidence: 99%
“…In this respect, the correlation between CAS and orbital MR imaging parameters is vital, but reports about the correlation between CAS and MR imaging parameters are limited [12,14,16]. The edematous change of the orbital tissue increases CAS, and prolongs T2RT of EOMs [2,6,15,17].…”
Section: The Comparison Of Cas 0 Group and Cas 1or2 Group In Maxt2rt mentioning
confidence: 99%
“…It appears likely that DTPA SPECT may be comparable to octreotide and other polypeptide SPECT results. The clinical usefulness of DTPA SPECT has been proven by several clinical studies from our institution [17]. Although factors of the initiation and perpetuation of the autoimmune process in GO remain unclear [18], quantitative data of orbital inflammation in GO are essential for appropriate treatment choices [19].…”
Section: Dtpa Uptake Values Other Diagnostic Methods and Treatment mentioning
confidence: 99%
“…This method has been accepted for evaluation of GO disease activity allowing a rapid imaging at an acceptable cost, and in addition, the successful management of GO has been associated with the decrease in orbital uptake of radiotracer [84]. In addition, to improve the sensitivity of detection of active GO phase, and therefore the prediction of the response to immunosuppressive therapy, over clinical activity score (CAS) alone, the combination of Tc-99m DTPA SPECT imaging and CAS estimation was proposed by Galuska et al [104]. They reported that Tc-99m DTPA SPECT imaging provides essential supplementary information to traditional CAS evaluation in assessing GO activity.…”
Section: Predicting Therapeutic Efficacy and Disease Activity Based Omentioning
confidence: 99%